The Deletion of IL-17A Enhances Helicobacter hepaticus Colonization and Triggers Colitis - Zhu L; Wu Z; Zhu C; Yin J; Huang Y; Feng J; Zhang Q (Dove Medical Press, 2022)
Liqi Zhu,1,2 Zhihao Wu,1,2 Chen Zhu,1,2 Jun Yin,1,2 Yuzheng Huang,3,4 Jie Feng,5 Quan Zhang1,2 1Institute of Comparative Medicine, College of Veterinary Medicine, Yangzhou University, Yangzhou, Jiangsu, 225009, People's Republic of China; 2Jiangsu Co-Innovation Center for Prevention and Control of Important Animal Infectious Diseases and Zoonoses, Yangzhou University, Yangzhou, Jiangsu, 225009, People's Republic of China; 3National Health Commission Key Laboratory of Parasitic Disease Control and Prevention, Jiangsu Provincial Key Laboratory on Parasite and Vector Control Technology, Jiangsu Institute of Parasitic Diseases, Wuxi, Jiangsu Province, 214064, People's Republic of China; 4Public Health Research Center, Jiangnan University, Wuxi, Jiangsu Province, 214122, People's Republic of China; 5Shanghai Laboratory Animal Research Center, Shanghai Quality Monitoring Center of Laboratory Animals, Shanghai, 201203, People's Republic of ChinaCorrespondence: Quan Zhang, Institute of Comparative Medicine, College of Veterinary Medicine, Yangzhou University, Yangzhou, People's Republic of China, Tel +86 138-1584-1244, Email zquan@yzu.edu.cnObjective: IL-17 is a key regulator of the inflammatory response, and as such, it is involved in the constraint and clearance of pathogens. The mechanism of IL-17 in the pathogenesis of inflammatory bowel disease (IBD) caused by microbial infection is still unclear. Helicobacter hepaticus infection can induce colitis in many mouse strains, and thus, it has been widely used in the study of IBD pathogenesis.Methods: In this study, male C57BL/6, BALB/c, Il-10−/−, and Il-17a−/− mice were infected with H. hepaticus for several weeks. Histopathology, H. hepaticus colonization and distribution, expression of inflammatory cytokines and lysozyme, and distribution of mucus in proximal colon were examined.Results: The colonic colonization of H. hepaticus was abnormally high in Il-17a−/− mice. H. hepaticus infection caused only mild to moderate colitis symptoms in Il-17a−/− mice, including low levels of lymphocyte infiltration, epithelial cell defects, goblet cell reduction, and crypt atrophy without obvious hyperplasia in the later stage of infection. Furthermore, many inflammatory genes were significantly increased in the proximal colon of H. hepaticus-infected Il-17a−/− mice compared with C57BL/6 mice. In addition, the reduction of colonic mucus and the down-regulation of ZO-1, Claudin-1, and IL-22 were observed in Il-17a−/− mice compared with C57BL/6 mice post H. hepaticus infection.Conclusion: These results demonstrated that the deletion of IL-17A impaired the integrity of the intestinal epithelium, weakened the secretion of mucus, attenuated colonic mucosal regeneration, reduced the ability to resist microbial infection, and finally led to colitis caused by H. hepaticus.Keywords: Helicobacter hepaticus, IL-17A, colitis, crypt atrophy